Incomplete specialization and offshoring across Europe - Richard Frensch; Jan Hanousek; Even Kocenda (FIW - Research Centre International Economics, 2012)
Recent empirical studies have been searching for evidence on and driving forces for offshoring. Frequently, this has been done by analyzing gross trade flows related to offshore activities using gravity equations augmented by ad hoc measures of supply-side country differences. This paper suggests that gravity formulations of this sort are mis-specified, due to theoretically unmotivated attempts to allow for both complete and incomplete specialization influences on gross trade flows within the same gravity framework. We suggest an alternative specification rooted in incomplete specialization that views bilateral gravity equations as statistical relationships constrained on countries' multilateral specialization patterns. This view reveals that countries' multilateral specialization incentives drive bilateral trade, corresponding to and competing with the role of multilateral trade resistance. Our results support evidence for offshoring activities across Europe, driven by countries' multilateral specialization incentives, as expressed by supply-side country differences relative to the rest of the world.
Keywords: F14; F16; L24; 330; International trade; gravity model; offshoring; panel data; European Union